Is South Africas Entrepreneurship Education Program Successful?: A Framework for Policy and Practice (Global Journal of Management and Business Research, 2021)
Entrepreneurship education has been adjudged as a process of building 21st-century skills, knowledge and inventive traits that are necessary for improving people's socioeconomic well being. The present COVID 19 pandemic, which has resulted in significant job losses makes it even more imperative for policymakers to prioritize entrepreneurial education and training in higher education. While there has been substantial progress in terms of stakeholder financial commitment towards developing entrepreneurship education in South African tertiary institutions, the same cannot be said for the quality of graduates produced. What can be done to address the challenge of low skill levels among South African university students? This conceptual paper examines the factors that restrict the success of entrepreneurship education programs in South African higher education using an in-depth assessment of relevant literature. It does so by examining the link between the existing policy framework and skill development strategies in the higher education sector. By using experiential learning theory, the article provides a framework that is designed to stimulate effective skill acquisition drive in the system. The paper further argues that, as part of their experiential approaches, tertiary institutions should provide entrepreneurship education that includes a wide range of life changing experiences such as; speed date competition, industrial tours, grooming, mentorship programs, and seminars, among others, these are imperative to enable students to absorb core skills, which is the real benchmark of a truly successful entrepreneurship education program.